Návrh měřicího zařízení pro kalibraci snímačů délky - Zindler, Lukáš (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2021)
Tato bakalářská práce se zabývá návrhem kalibračního zařízení pro indukčnostní snímač délky. V teoretické části je zpracován základní přehled v metrologii a stav poznání v oblasti snímačů. V praktické části je navrhnuto několik konceptů měřících přípravků, vybráno a sestaveno vhodné kalibrační zařízení a na závěr provedena kompenzace systematické chyby snímače.

This study aimed deals with the design of a calibration equipment for an inductive distance sensor. The theoretical part provides a basic overview of metrology and the state of knowledge in the field of sensors. In the practical part, several concepts of measuring equipment are suggested, a suitable calibration equipment is selected and assembled, and at last the compensation of the systematic error of the sensor is performed.
Design of a measuring equipment for distance sensors calibration
Keywords: Návrh zařízení; snímače; indukčnostní snímače; kompenzace chyby; metrologické pojmy; Equipment design; sensors; inductive sensors; error compensation; metrological concepts